1989
DOI: 10.1099/0022-1317-70-6-1391
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetic Control of Incubation Periods of Creutzfeldt-Jakob Disease in Mice

Abstract: SUMMARYHost genetic control of the incubation period of Creutzfeldt-Jakob disease (CJD) was studied using various inbred strains of mice, including B10 congenic strains. Various incubation periods were found in mice injected either intracerebrally or intraperitoneally with the Fukuoka 1 strain of the CJD agent; NZW/Sea and A/JJms had the shortest, and BI0.AKM/OIa and C57BL/6J the longest, incubation periods. Length of the CJD incubation period did not correlate with the genetic markers tested, i.e. the murine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
4
2
Order By: Relevance
“…Previous reports suggested a QTL for incubation time on chromosome 17 within the H2 locus of the major histocompatibility complex, although this was not replicated by others or identified in our cross (18,34). However, challenge with different prion strains by different routes of inoculation and in other strains of mice may result in the segregation of alternative susceptibility genes.…”
Section: Resultscontrasting
confidence: 88%
“…Previous reports suggested a QTL for incubation time on chromosome 17 within the H2 locus of the major histocompatibility complex, although this was not replicated by others or identified in our cross (18,34). However, challenge with different prion strains by different routes of inoculation and in other strains of mice may result in the segregation of alternative susceptibility genes.…”
Section: Resultscontrasting
confidence: 88%
“…The H-2D-linked effect, initially detected in congenic mouse strains infected with mouse-adapted CJD, has failed to be replicated by us or other investigators (33,34). Finally, although we do know that there are differences in the promoter region of the Prnp gene between the C57BL and RIII mouse strains, we do not detect any effect linked to the Prnp gene.…”
Section: Discussioncontrasting
confidence: 43%
“…Comparison of incubation periods for ME7, 139A and 22L versus that of 22A clearly establishes that the mouse strains used in these studies have the s(s( genotype. It has been shown that different mouse strains within the same Sinc genotype, for example s(s(, can have different incubation periods for the same TSE strain (Kingsbury et al, 1983 ;Carp & Callahan, 1986 ;Dickinson & Outram, 1988 ;Mohri & Tateishi, 1989). Scrapie incubation period differences within the s(s( group of mice have been shown to be a function, in part, of H-2D locus (Kingsbury et al, 1983 ;Carp & Callahan, 1986).…”
Section: Discussionmentioning
confidence: 99%